A DISCOURSE ANALYSIS OF THE LINGUISTIC FEATURES OF PERFORMATIVE SENTENCES IN CERTIFICATES AND DEGREES IN ENGLISH VERSUS VIETNAMESE - Ph.D. Ngũ Thiện Hùng, Assoc. Prof. Dr. TRẦN VĂN PHƯỚC (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study is intended to investigate the linguistic features of performative sentences in certificates and degrees in English vs. Vietnamese to help English learners and teachers have a better insight of the performative sentence. The data used in observation and analysis are taken from 400 examples including English and Vietnamese certificates and degrees. Through this study, a qualitative analysis and a descriptive approach have been done to find out the semantic and pragmatic features of performative sentences which are used based on the various contexts as well as syntactic features. In syntactic aspect, the study showed the three main structures of the performative sentence, ‘S/V/O/C’, ‘S/V/O/O/C’ and ‘S/V/O/C/A’. In semantic aspect, the Vietnamese equivalents of performative verbs used in certificates and degrees are listed. In pragmatic aspect, this study presented that both English and Vietnamese performative sentences in certificates and degrees satisfied the conditions of declaration speech acts. Moreover, the data analysis showed three main parts in the layout of certificates and degrees in English and Vietnamese. Last but not least, this study presented some remarks of similarities and differences between English and Vietnamese based on the layout, syntactic, semantic and pragmatic features. Hopefully, the study will bring practical benefits to compile and translate certificates and degrees.